Pengaruh Persepsi Harga Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Pada Situs Belanja Online Shopee - Grace Yosephine Benjamin; Mumuh Mulyana (Jurnal Informatika Kesatuan, 2022)
Purchasing Decisions are purchasing decisions define that purchasing decisions are part of consumer behavior i.e. the study of how individuals, groups, and organizations choose, buy, use and how goods, services, ideas or experiences to satisfy their needs and desires is a public offering made to sell securities to society involving goods or services to consumers in smaller quantities aimed at consuming them or used it personally and couldn't resell it. Electronic world of Mouth (E-WOM) is a positive or negative statement made by potential, actual, or former consumers about a company's products or services through the internet. This study aims to analyze the influence of Price Perception and Electronic world of Mouth (E-WOM) on Purchasing Decisions on the Shopee online shopping site. Empirical Study on Shopee Customers in Bogor City. The type of data used is Primary data derived from the Respondent Questionnaire. The sample of this study amounted to 110 samples using the likert scale method which came from 110 number of respondents who corresponded to shopee users in the city of Bogor. in this study the data were analyzed using multiple linear analysis with the help of SPSS. The results of this study show that Price Perception affects Purchasing Decisions. Meanwhile, the Electronic world of Mouth (E-WOM) has no effect on purchasing decisions. Then simultaneously, showing Price Perception, and Electronic world of Mouth (E-WOM) affects purchasing decisions. Keywords: Price Perception, Electronic world of Mouth (E-WOM), Purchasing Decision